Degradation of Azo Dye (Acid Orange 7) in a Microbial Fuel Cell: Comparison Between Anodic Microbial-Mediated Reduction and Cathodic Laccase-Mediated Oxidation - Mani, Priyadharshini; Fidal, V. T.; Bowman, Kyle; Breheny, Mark; Chandra, T. S.; Keshavarz, Taj; Kyazze, Godfrey (Frontiers in Energy Research, 2019)
More than 80 per cent of wastewater from industries is discharged into receiving water bodies without any pollution control. Microbial fuel cells (MFCs) are a promising technology for the simultaneous treatment of wastewater and electricity production. With regard to azo-dye containing wastewater (e.g. from textile manufacturing), the dye may be fed via the anode chamber containing electrochemically active bacteria or via the cathode chamber containing laccase enzyme as catalyst for oxygen reduction. This study investigated which of the two approaches is the best with regard to rate of decolourization of the dye (Acid orange 7), COD reduction and electricity production. The power density was higher for the MFCDye cathode (50±4 mW m-2, COD reduction 80.4±1.2%) compared with 42.5±2.6 mW m-2 (COD reduction 69±2%) for MFCDye anode. The time required for decolourization was longer in the MFCDye anode (Shewanella oneidensis) where only 20% decolourization was obtained after 24 h compared to 80% for the MFCDye cathode. The anodic dye degradation products were unstable when exposed to air resulting in regaining of colour. In case of degradation by laccase in the cathode chamber, the decolourization products were stable and simpler in chemical structure as determined by GC-MS. This work suggests that feeding azo dyes in cathode chambers of MFCs containing laccase is a better way of treating the dyes compared to the commonly used approach of feeding the dye in the anode chamber provided enzyme activity can be sustained.